1994
DOI: 10.1007/bf00380781
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, metabolism and elimination of cyclohexanone in humans

Abstract: The metabolism and toxicokinetics of cyclohexanone (CH-one), an important solvent and chemical intermediate, have been studied in volunteers during and after 8-h exposures to CH-one vapour at a concentration of 101, 207 and 406 mg.m-3. The pulmonary ventilation in these experiments was typically 11 l.min-1 and retention in the respiratory tract was 58%. After exposure to CH-one, 207 mg.m-3, the metabolic yields of cyclohexanol (CH-ol), 1,2- and 1,4-cyclohexanediol (CH-diol) as determined in urine by a gas chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Cyclohexanol and cyclohexanone were found in the urine of these workers, indicating that the same metabolic pathways are also found in humans (Governa et al, 1987). A recent study in humans shows that the main metabolite in urine after cyclohexanone or cyclohexanol exposure is not cyclohexanolglucuronide as in rabbit and rats, but 1,2-cyclohexanediol-glucuronide (Mráz et al, 1994;Mráz et al, 1998).…”
Section: Iii24 Metabolism To Glucuronidesmentioning
confidence: 59%
“…Cyclohexanol and cyclohexanone were found in the urine of these workers, indicating that the same metabolic pathways are also found in humans (Governa et al, 1987). A recent study in humans shows that the main metabolite in urine after cyclohexanone or cyclohexanol exposure is not cyclohexanolglucuronide as in rabbit and rats, but 1,2-cyclohexanediol-glucuronide (Mráz et al, 1994;Mráz et al, 1998).…”
Section: Iii24 Metabolism To Glucuronidesmentioning
confidence: 59%
“…Only the values at the end of the shift are important for threshold limit evaluation. In addition, Mraz et al (1994) have shown that, during an exposure lasting several days, an increase in diol excretion occurs which is 60 % higher on day 3 than on day 1. According to calculations in the BEI documentation of the ACGIH (ACGIH 2004), the corresponding excretion values in the post-shift samples after an exposure to 20 ml cyclohexanone/m 3 are 58 mg 1,2-cyclohexanediol/l urine on day 1 and 82 mg/l urine on day 3.…”
Section: Relationship Between External and Internal Exposurementioning
confidence: 98%
“…Three field studies (Kawai et al 1999;Ong et al 1991a, b) and three laboratory studies from one working group (Mraz et al 1994(Mraz et al , 1998(Mraz et al , 1999 are available for the evaluation of a correlation, which is mainly based on two investigations. Kawai et al (1999) investigated 24 workers who had been exposed to a solvent mixture with cyclohexanone as a component.…”
Section: Relationship Between External and Internal Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in humans shows that the main metabolite in urine after cyclohexanone or cyclohexanol exposure is not cyclohexanol-glucuronide as in rabbit and rats, but 1,2-cyclohexanediolglucuronide (Mráz et al, 1994;Mráz et al, 1998).…”
Section: C2 Biotransformationmentioning
confidence: 98%